The Creation of Lived Public Spaces by African Migrants and People of Diverse Ethnicity in the Pretoria CBD and its Implications for Urban Planning A Phenomenological Investigation - Vosloo, Pieter Tobias (University of Pretoria, 2022)
Thesis (PhD)--University of Pretoria, 2019.